A systemic review of yak milk and its products on the Qinghai-Tibet Plateau: Unique products, chemical composition, biological activities, and microbial composition - Zhiqiang Liang; Xiaoqian Chen; Xinyu Wang; Xiaoxi Qi; Lina Zhang; Yu Xin; Zhenyu Yang; Rui Fan; Yang Li; Libo Liu; Chun Li (Trends in Food Science & Technology, 2024)

Exploring the spatiotemporal evolution patterns of Urban Heat Island with a network-based approach - Kang Zou; Xinyu Yu; Man Sing Wong; Kai Qin; Rui Zhu; Songyang Li (Sustainable Cities and Society, 2024)

Improving the affordability and reducing greenhouse gas emissions of the EAT-Lancet diet in China - Meng Li; Yanan Wang; Shunan Zhao; Wei Chen; Yu Liu; Heran Zheng; Zhongxiao Sun; Pan He; Rui Li; Sun Zhang; Peixue Xing; Qiao Li (Sustainable Production and Consumption, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Urine multi-omics markers to predict seizure one day in advance - Wanlin Lai; Leihao Sha; Rui Li; Shan Yu; Ling Jin; Ruiqi Yang; Chao Yang; Lei Chen (Science Bulletin, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

Contribution of alkaline magmas to the petrogenesis of Triassic aluminous A-type granites on Liaodong Peninsula, Northeastern China - Yu-Sheng Zhu; Jin-Hui Yang; Jin-Feng Sun; Jing-Yuan Chen; Lei Xu; Rui Li; Bao-Quan Zhou (Lithos, 2024)

Application of metallic minerals in wastewater treatment: A review - Xuchao Sun; Yinghao Tang; Rui Li; Kaizhen Wu; Fang Shen; Shiping Zhang; Lutao Xue; Yu Jiang; Xiaoyong Wu (Journal of Water Process Engineering, 2024)

Boosting light harvesting and charge separation in Au nanoparticles and g-C3N4 co-modified TiO2 nanotube arrays for efficient photoelectrocatalytic reduction of nitrate in water - Rui Xu; Yong Guan; Lixue Cao; Xiaoxi Yu; Linsen Li; Bingrui Ma; Chunwei Liu (Journal of Water Process Engineering, 2024)

Ultrabright silicon nanoparticles combined with o-phenylenediamine for ratiometric fluorescence and smartphone imaging dual-mode detection of nitrite - Wen-Jie Gao; Ming-Yue Tian; Xing-Hui Ren; Hao-Rui Zhang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Thermodynamic characteristics of nitrifiers reveal the potential NOB inhibition strategies at low temperatures - Ren Li; Lifang Yu; Rui Jiang; Tian Liu; Zhuoya Li; Dangcong Peng (Journal of Cleaner Production, 2024)

Recovery of low-concentration waste acid by electrodialysis: Modeling and validation - Feng-rui Li; Yu-xiang Jia; Meng Wang (Journal of Cleaner Production, 2024)

Vacuum-thermal alteration of lunar soil: Evidence from iron whiskers on troilite in Chang’e-5 samples - Chen Li; Yang Li; Kuixian Wei; Xiumin Chen; Kairui Tai; Zhuang Guo; Rui Li; Han Yu; Xiongyao Li; Wenhui Ma; Jianzhong Liu (Geochimica et Cosmochimica Acta, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Insights into carbon-neutral treatment of rural wastewater by constructed wetlands: A review of current development and future direction - Feifei Jiao; Xinzheng Zhang; Tao Zhang; Yong Hu; Rui Lu; Guangyi Ma; Tao Chen; Hongbo Guo; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Environmental Research, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Deep Learning Based Diagnosis of Mild Cognitive Impairment Using Resting-State Functional MRI - Guangyao Li; Yalin Song; Huimin Liang; Xiaoman Sun; Junyang Yu; Rui Zhai; Mingyang Liang (Journal of Medical and Biological Engineering, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Phylogenomic analyses and comparative genomic studies of Thermus strains isolated from Tengchong and Tibet Hot Springs, China - Inam Ullah Khan; Muhammad Saqib; Arshia Amin; Sadia Manzoor; Iftikhar Ahmed; Rui-Rui Liu; Jian-Yu Jiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

The effect of green coffee extract supplementation on obesity indices: critical umbrella review of interventional meta-analyses - Zhao Yang; Zhuo Shao; Weiyi Ouyang; Lu Ying; Rui Guo; Mingxuan Hao; Youfeng Liang; Wenjing Zhang; Xiaoyang Chen; Ruolan Chen; Changyuan Yu; Kousalya Prabahar; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Economic, institutional and environmental drivers of SMEs’ development in the EU: sustainable development goals perspective - Yu-Xia Tu; Oleksandr Kubatko; Leonid Melnyk; Rui Li; Bohdan Kovalov; Anastasia Yaremenko (Environment, Development and Sustainability, 2024)

Anxiety caused by chronic exposure to methylisothiazolinone in zebrafish: Behavioral analysis, brain histology and gene responses - Rui Li; Jiangbo Qu; Xinyuan Hu; Tianjia Song; Junxia Hu; Xuesong Fan; Yuanqing Zhang; Weili Xia; Tiangui Yu (Chemosphere, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Synergistic effects and comprehensive analysis of interaction during infrared co-pyrolysis of furfural residues and PVC - Yue Zhang; Moshan Li; Zuohua Liu; Jianglong Yu; Erfeng Hu; Rui Qu; Shuai Li (Process Safety and Environmental Protection, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Regulation of anthocyanin synthesis in red lettuce in plant factory conditions: A review - Hadiqa Anum; Kun Li; Javaria Tabusam; Said Abdelhalim Abdelaty Saleh; Rui-feng Cheng; Yu-xin Tong (Food Chemistry, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Historical assessment and future scenario modelling: How do inter-provincial migrants affect the process of carbon peaking in residential buildings? - Yanhui Yu; Rui Li; Weiguang Cai; Kairui You (Environmental Impact Assessment Review, 2024)

Zirconium based metal–organic frameworks with aggregation-induced electrochemiluminescence for sensitive analysis of aflatoxin B1 by signal dual-amplification strategy - Yuan Li; Xue Dong; Tingting Wu; Xiaoyue Zhang; Xiang Ren; Rui Feng; Yu Du; Jin Yong Lee; Xuejing Liu; Qin Wei (Chemical Engineering Journal, 2024)

Manipulating surface reconstruction and lattice oxygen mechanism of nickel (oxy)hydroxide by defect engineering for industrial electrocatalytic water oxidation - Xiangling Wang; Zhimin Li; Yu Tang; Zhengfu Zhang; Chengping Li; Rui Bao; Guo Chen; Jinsong Wang (Chemical Engineering Journal, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

A superior material with antithrombotic properties serves as a secure adsorbent for the elimination of bilirubin in vitro and in pig models - Rui Su; Wei Liu; Gang Shi; Dongling Chen; Lihua Yan; Qian Li; Haichao Ni; Meili Yu; Liang Xu (Chemical Engineering Journal, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

Defining watershed-scale sediment delivery ratio using functional connectivity: Exploring the relationship between monthly-scale sediment delivery ratio and soil erosion — A case study from a karst watershed - Linlv Xiao; Benjin Yu; Rui Li; Panpan Wu; Feiyang Cai (CATENA, 2024)

Phthalates on indoor surfaces and associated exposure via surface touch behavior: Observation in university dormitories and its implications - Fangzhou Yuan; Yu Sun; Na Li; Jianping Cao; Nan Zhang; Daniel Mmereki; Zhonghua Wei; Rui Chen; Jinyu Zhou; Yousheng Xu; Zhongming Bu (Building and Environment, 2024)

Simulation of a cold spell in Guangdong-Hong Kong-Macao Greater Bay Area with WRF: Sensitivity to PBL schemes - Rui Xin; Xian-Xiang Li; Yu Du; Minghua Li; Lup Wai Chew (Atmospheric Research, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Association of Plasma Metal Levels with Outcomes of Assisted Reproduction in Polycystic Ovary Syndrome - Dan Yin; Rui Mao; Die Wang; Ping Yu; Cuilan Zhou; Jun Liu; Suyun Li; Yulin Nie; Hongqing Liao; Cuiying Peng (Biological Trace Element Research, 2024)

Geographic variation in leaf traits and palatability of a native plant invader during domestic expansion - Yu‐Jie Zhao; Shengyu Wang; Zhi‐Yong Liao; Madalin Parepa; Lei Zhang; Peipei Cao; Jingwen Bi; Yaolin Guo; Oliver Bossdorf; Christina L. Richards; Jihua Wu; Bo Li; et al. (Ecology, 2024)
Like alien plant invasion, range expansion of native plants may threaten biodiversity and economies, rendering them native invaders. Variation in abiotic and biotic conditions across a large geographic scale greatly affects variation in traits and interactions with herbivores of native plant invaders, which is an interesting yet mostly unexplored issue. We used a common garden experiment to compare defensive/nutritional traits and palatability to generalist herbivores of 20 native (23.64° N–30.18° N) and introduced range (31.58° N–36.87° N) populations of Reynoutria japonica , which is a native invader following range expansion in China. We analyzed the relationships among herbivore pressure, climate, plant chloroplast haplotypes, leaf traits, and herbivore performance. Of the 16 variables tested, we observed range differences in 11 variables and latitudinal clines in nine variables. In general, herbivores performed better on the introduced plants than on the native plants, and better on the high‐latitude plants than on the low‐latitude plants within the introduced populations. Three key traits (leaf thickness, specific leaf area, and carbon‐to‐nitrogen [C:N] ratio) determined palatability to herbivores and were significantly associated with temperature and/or precipitation of plant provenance as well as with plant haplotypes but not with herbivore pressure. Our results revealed a causal sequence from plant‐range‐based environmental forces and genetic context to plant quality and palatability to herbivores in R. japonica . These findings suggest a post‐introduction evolution of R. japonica , which may partly explain the colonization success of this important native, but invasive plant.

The role and function mechanism of tapP in modulating the virulence of Aeromonas hydrophila - Rui Long; Jinming Wei; Caijiang Xiong; Bei Wang; Jiahui Lu; Hua Ye; Yun Li; Yongyao Yu; Lingyun Lin; Ronghua Wu (Aquaculture, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Exploring the gradient impact of climate and economic geographical factors on city-level building carbon emissions in China: Characteristics and enlightenments - Rui Li; Yanhui Yu; Weiguang Cai; Yuan Liu; Yan Li (Sustainable Cities and Society, 2024)

The presences of water in the generation of calc-alkaline I-type granitic magmas at continental arc: Insight from Neoproterozoic Ailaoshan magmatism at the southwestern margin of the Yangtze Block, South China - Bin Huang; Rui Li; Nimat Ullah Khattak; Xin-Yu Cai; Yang Zhang; Wei Wang (Precambrian Research, 2024)

Nano Fe3O4 improved the electron donating capacity of dissolved organic matter during sludge composting - Liu Chen; Zeyu Zhang; Rui Yang; Xiaojie Wang; Jieyu Yu; Hong Jiang; Wenjie Zhang; Beidou Xi; Xiaojie Sun; Ningjie Li (Journal of Environmental Management, 2024)

Disinfection of bacteria and viruses under near infrared light by tunable self-assembled nanomaterial NH2-MIL-101-xAu based on photothermal and photodynamic mechanisms - Nian Li; Zi-jian He; Jia-min Gan; Xing-rui Qi; Shu-nuo Bian; Yu-fang Chen; Bo Liu; Hua-jie Lai; Tao Jin (Journal of Environmental Chemical Engineering, 2024)

Reducing moisture content can promote the removal of pathogenic bacteria and viruses from sheep manure compost on the Qinghai-Tibet Plateau - Rongrong Li; Rui Cai; Xi Luo; Yuru Liu; Lu Zhang; Wenbo Yu; Zhe Yang (Journal of Environmental Chemical Engineering, 2024)

In situ synthesized Ag nanoparticles encapsulated inside carbonized ZIF-8 for efficient Cr(VI) reduction - Haojie Zhang; Zhuo-Rui Jiang; Yu-Xiao Zhou; Rui Chen; Hongmei Jiang; Ying Li (Journal of Environmental Chemical Engineering, 2024)

Enhanced photocatalytic Cr(VI) degradation and real-time detection using dual-fluorescent quantum dot-infused polysulfone microspheres - Rui Zhao; Feihong Hu; Shan Li; Chao Liu; Zhiwei Wang; Zhaoping Song; Dandan Ji; Xiaona Liu; Huili Wang; Wenxia Liu; Fengshan Zhang; Dehai Yu (Journal of Environmental Chemical Engineering, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Controlled dispersion and morphology in MoS2/SBA-15 catalysts for enhanced COS hydrodesulfurization - Li Yubiao; Cao Rui; Liu Yu; Wang Langlang; Ning Ping; Wang Xueqian; Ma Yixing (Fuel, 2024)

Enhancement of bio-jet fuel production from corncob by iron ion-catalyzed hydrogen peroxide pretreatment - Rui Zhang; Yuting He; Rui Zhu; Can Zhu; Yu Jiang; Yuming Ni; Minghui Fan; Quanxin Li (Fuel, 2024)

Colorimetric sensing based on silver nanoparticle-functionalized copper porphyrin nanozyme for glyphosate - Li-Hong Yu; Rui Jiang; Cheng-Lin Yang; Yue-Hong Pang; Xiao-Fang Shen (Food Bioscience, 2024)

Metabolomics combined with intestinal microbiota analysis to reveal the effects of Inonotus hispidus on chronic kidney disease caused by high-protein diet - Xin Pang; Zitao Guo; Long Ao; Yong Huang; Bo Hu; Zhenghua Gu; Yu Xin; Zhongpeng Guo; Rui Zhu; Moying Li; Liang Zhang (Food Bioscience, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Quantitative evaluation method for post-earthquake functionality loss of pedestrian flow pathways within a complex building using evacuation and rescue simulation - Zhao-Long Shi; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Han Zhang; Rui Wang (Engineering Structures, 2024)

LCZ-based city-wide solar radiation potential analysis by coupling physical modeling, machine learning, and 3D buildings - Xiana Chen; Wei Tu; Junxian Yu; Rui Cao; Shengao Yi; Qingquan Li (Computers, Environment and Urban Systems, 2024)

Understanding Partial Denitrification-hydroxyapatite (PD-HAP) coupled granules to enhance process stability and phosphorus removal by investigating the size effect of granules - Jinxin Fang; Yu Lan; Rui Du; Jiawei Ren; Xing Li; Xiaoyan Fan; Shenbin Cao (Chemical Engineering Journal, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

Enhancing reaction kinetics in aprotic magnesium-air batteries using a freestanding flexible metal-free carbon fiber cathode - Wenbo Liu; Ning Wang; Rui Zhong; Fanfan Liu; Yongjun Wu; Qianyi Zhang; Xiaoyan Chen; Yanmei Li; Minghui Yu; Rui Xu; Yifei Yuan; Dan Luo; et al. (Chemical Engineering Journal, 2024)

Highly stretchable, self-healing, antibacterial, conductive, and amylopectin-enhanced hydrogels with gallium droplets loading as strain sensors - Feihong Hu; Baoting Dong; Dehai Yu; Rui Zhao; Wei Chen; Zhaoping Song; Peng Lu; Fengshan Zhang; Zhaojiang Wang; Xiaona Liu; Huili Wang; Wenxia Liu; et al. (Carbohydrate Polymers, 2024)

Arbuscular Mycorrhizal Fungi Enhance Tolerance to Drought Stress by Altering the Physiological and Biochemical Characteristics of Sugar Beet - Zeyuan Cui; Rui Chen; Tai Li; Bingchen Zou; Gui Geng; Yao Xu; Piergiorgio Stevanato; Lihua Yu; Vadim N. Nurminsky; Jiahui Liu; Yuguang Wang (Sugar Tech, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

DDLA: a double deep latent autoencoder for diabetic retinopathy diagnose based on continuous glucose sensors - Rui Tao; Hongru Li; Jingyi Lu; Youhe Huang; Yaxin Wang; Wei Lu; Xiaopeng Shao; Jian Zhou; Xia Yu (Medical & Biological Engineering & Computing, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Optimizing waste leachate treatment for environmental and economic sustainability: Insights from a bottom-up study of over 300 cities - Qian-long Han; Hai-long Zhao; Guo-xia Wei; Han-qiao Liu; Yu-wen Zhu; Tong Li; Yan-fei Lin; Xin-rui Su (Sustainable Production and Consumption, 2024)

Semi-liquid metal-based highly permeable and adhesive electronic skin inspired by spider web - Rui Guo; Xiaoqing Li; Yingtong Zhou; Yuqi Zhang; Chengjie Jiang; Yang Yu; Qingting Tan; Wenbo Ding; Hongzhang Wang (Science Bulletin, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Anaerobic oxidation of methane and greigite formation: Evidence of isotopically heavy pyrite in Pleistocene coastal sediments from the South Yellow Sea - Xiaoxiao Yu; Xi Mei; Jianxing Liu; Baichuan Duan; Rui Zhang; Tiegang Li; Gangjian Wei; Mang Lin (Global and Planetary Change, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

OsSPL11 positively regulates grain size by activating the expression of GW5L in rice - Xinhai Zeng; Kai Fan; Yu Shi; Rui Chen; Wanyu Liu; Xin Wang; Guixiang Ye; Wenxiong Lin; Zhaowei Li (Plant Cell Reports, 2024)

Farrerol Alleviates Cerebral Ischemia–Reperfusion Injury by Promoting Neuronal Survival and Reducing Neuroinflammation - Rui Zhao; Xin Zhou; Zhiyuan Zhao; Wenhao Liu; Mengfei Lv; Zhaolong Zhang; Changxin Wang; Tianli Li; Zixiong Yang; Qi Wan; Rui Xu; Yu Cui (Molecular Neurobiology, 2024)

Climate risk analysis of low-altitude tea gardens in central Taiwan using a Bayesian network - Yung-Chieh Wang; Chien-Teh Chen; Rui-Yu Li; Yu-Hsin Lu; Li-Chi Chiang (Environmental Monitoring and Assessment, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

Adaptation mechanisms of soil microbial community to stoichiometric imbalances caused by forest conversion - Xianzhen Luo; Lingling Zhang; Zhi Li; Rui Zhang; Johannes J. Le Roux; Jason K. Reynolds; Hanxia Yu; Minghao Chen; Yahong Zheng; Enqing Hou; Dazhi Wen (Applied Soil Ecology, 2024)

Goose grazing shifts the dominance of annual vegetation in coconut plantations from aboveground biomass to the soil seed bank - An Hu; Zhiyuan Wei; Qianzhen Dong; Rongshu Dong; Weibo Yang; Ruoyun Yu; Rui Zhang; Xinyong Li (Agriculture, Ecosystems & Environment, 2024)

Design and synthesis of ligustrazine derivatives as potential anti-Alzheimer’s agents - Xu-fei Chen; Shan-shan Li; Yu-jun Bai; Ze-feng Zhao; Ya-jun Bai; Gu Gong; Xi-rui He; Xiao-hui Zheng (Natural Product Research, 2024)

Characterization and source apportionment of pharmaceuticals in surface water of the Yangtze Estuary and adjacent sea - Chunzhao Chen; Jian Tang; Fei Li; Rui Xue; Yihua Xiao; Ling Chen; Gang Yu (Environmental Science and Pollution Research, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

Late Pliocene Bauhinia s.l. (Cercidoideae, Fabaceae) fossils from Tengchong, Yunnan, southwestern China - Rui Cao; Zhi-hui Song; Zhuo-er Wang; Zhao-shuai Wang; Han-shi Li; Jing-Yu Wu; Su-Ting Ding (Review of Palaeobotany and Palynology, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Extended applications of the small-scale radio frequency system for improving the heating performance of multi-component rice - Yingqi Tian; Haibo Yu; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Highly selective and sensitive immunoassays for flurogestone acetate analysis in goat milk: From rational hapten design and antibody production to assay development - Rui Liu; Xingya Sun; Yingjie Zhang; Peipei Li; Li Nan; Qing Shen; Kai Wen; Xuezhi Yu; Jianzhong Shen; Yantong Pan; Zhanhui Wang (Food Chemistry, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Effect of chitooligosaccharides in inhibiting textural deterioration of chicken myofibril protein gel induced by high temperature - Yuntao Wang; Jing Chen; Rui Li; Shasha Wang; Ke Li; Yu Wang; Si Qiu; Dianbo Zhao; Yanhong Bai (Food Hydrocolloids, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Highly nanostructured and carboxylated wood aerogel-based adsorption membrane reconstructed by grafting of polyacrylic acid for efficient removal of heavy-metal ions - Wen He; Bairen Wei; Shuang Liang; Rui Wang; Qiulin Ji; Gangzheng Hu; Wenxuan Li; Lei He; Juan Yu; Hongfei Zhu; Kaiyin Wang (Chemical Engineering Journal, 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Targeting gut microbiota for immunotherapy of diseases - Ya-Jie Yu; Xiao-Dong Liu; Cai Liao; Rui Yu; Xin Wang; Ming Li; Yun Wang (Archives of Toxicology, 2024)

Formation and growth of nanophase iron particles on the surface of Mercury revealed by experimental study - Ronghua Pang; Yang Li; Chen Li; Pengfei Zhang; Zhuang Guo; Sizhe Zhao; Han Yu; Li Wang; Chenxi Zhu; Shuangyu Wang; Kairui Tai; Qinwei Zhang; et al. (Acta Geochimica, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

Boosting peroxymonosulfate activation over partial Zn-substituted Co3O4 for florfenicol degradation: Insights into catalytic performance, degradation mechanism and routes - Xinyang Wang; Xinyu Luo; Rui Li; Yu Chang; Jianbiao Peng; Weilai Wang; Haijin Liu; Guangxuan Yan; Pengkun Wei; Zhiguo Cao (Chemical Engineering Journal, 2024)

Toxic Metal Soil Speciation, Corn Accumulation and Health Risk Assessment in Acidic red soil Farmland in Mineral Industry Area - Yu Qian; Xiaoqi Li; Jie Yang; Rui Zhou; Zijin Hong; Change Liu; Shiyu Li; Yonggui Zhao; Denggao Fu; Ying Pan; Huan Feng; Marek Kolenčík; et al. (Water, Air, & Soil Pollution, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

P53 upregulation by USP7-engaging molecular glues - Zhaoyang Li; Ziying Wang; Chao Zhong; Hang Zhang; Rui Liu; Ping An; Zhiqiang Ma; Junmei Lu; Chengfang Pan; Zhaolin Zhang; Zhiyuan Cao; Jianyi Hu; et al. (Science Bulletin, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Facet effect on nanosheet Co3O4 catalysts for toluene oxidation: Decisive role of Co3+ and reaction-induced oxygen vacancy - Rui Liu; Yuting Chu; Yiming Li; Kaijie Li; Tong Li; Hongbo Yu; Rui Liang; Yipei Chen; Tao Wu; Hongfeng Yin (Journal of Environmental Chemical Engineering, 2024)

Synthesis, characterization, and environmental evaluation of Fe-PCN-134: A mixed-linker metalloporphyrin MOF for the degradation of atrazine via visible photo-Fenton reaction - Meng Yu; Yinmin Wang; Yingjian Ma; Zhe Sun; Li Ma; Shouhe Pan; Rui Zhao; Xinyu Guo; Yong Xu; Xuemin Wu (Journal of Environmental Chemical Engineering, 2024)

Developing a combined rotating and air-circulating system for improving radio frequency heating uniformity and controlling Aspergillus in almond kernels - Rui Li; Yu Gao; Junjie Zheng; Mengge Li; Yujun Hao; Longlong Jiang; Shunqin Bai; Dingting Zhou; Juanjuan Xu; Xiaoxi Kou; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Experimental study on reinjection enhancement of sandstone with radial wells - Chao Yu; Kang Cheng; Zhongwei Huang; Jingbin Li; Jingru Hu; Dong Yang; Rui Li (Geothermics, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

High-spatial resolution ground-level ozone in Yunnan, China: A spatiotemporal estimation based on comparative analyses of machine learning models - Xingwei Man; Rui Liu; Yu Zhang; Weiqiang Yu; Fanhao Kong; Li Liu; Yan Luo; Tao Feng (Environmental Research, 2024)

Highspeed transport pathway dominated by continuous arrangement of micron-sized hollow MOFs in MMMs to accelerate CO2 permeation - Wenji Zheng; Rui Ding; Ziheng Li; Xuehua Ruan; Yan Dai; Miao Yu; Xiangcun Li; Xiaoming Yan; Xiaobin Jiang; Xiujuan Zhang; Gaohong He (Chemical Engineering Journal, 2024)

Lipoic acid/trometamol assembled hydrogel as injectable bandage for hypoxic wound healing at high altitude - Rui Lei; Mingbao Gu; Jinyan Li; Wenjun Wang; Qian Yu; Rizwan Ali; Jiajia Pang; Meilun Zhai; Yang Wang; Kunxi Zhang; Jingbo Yin; Jinghong Xu (Chemical Engineering Journal, 2024)

C@MOF composite material for rapid and efficient capture of gaseous iodine - Rui-Li Yu; Mei-Qi Sun; Xiao-Yu Wang; Dao-Tong Li; Zhen-Le Li; Liang-Zhi Xia (Chemical Engineering Journal, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Preparation of crab-shell-based N, O co-doped graded porous carbon for supercapacitors using the confined nanospace deposition method - Yiming Li; Zhihao Yu; Mengyan Guo; Ming Zhang; Jian Xiong; Yina Qiao; Rui Zhang; Xuebin Lu (Waste Disposal & Sustainable Energy, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Genome-wide identification and expression-pattern analysis of sulfate transporter (SULTR) gene family in cotton under multiple abiotic stresses and fiber development - Yu Chen; Xianghui Xiao; Rui Yang; Zhihao Sun; Shuhan Yang; Haibo Zhang; Baoguang Xing; Yanfang Li; Qiankun Liu; Quanwei Lu; Yuzhen Shi; Youlu Yuan; et al. (Functional & Integrative Genomics, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

3D gravity inversion using cycle-consistent generative adversarial network - Shu-Bo Qiao; Hou-Pu Li; Rui Qi; Yu-Jie Zhang; Shi-Min Xie (Applied Geophysics, 2024)

Investigation of 200 anthropogenic activities in a representative alpine peatland in the Altay Mountains, northwestern China - Nana Luo; Rui Yu; Bolong Wen; Xiaoyu Li; Qilin Zhang; Xiujun Li (Environmental Science and Pollution Research, 2024)
Peatlands records can be used to reconstruct and understand the history of environmental evolution, as well as a more accurate reflection of human activities. The black carbon (BC) and polycyclic aromatic hydrocarbons (PAHs) are ideal natural archives of anthropogenic activities. To identify the information of anthropogenic activities recorded by peatlands in the middle and high latitudes of the alpine mountains in the arid and semi-arid regions of China. this study analyzed the concentrations of BC, δ 13 C ratios of BC, PAHs, and molecular diagnostic ratios of PHAs (including Benzo(a) anthracene (BaA), Chrysene (Chr), fluoranthene (Flt), anthracene (Ant), phenanthrene (Phe), Benzo(a) pyrene (BaP), and pyrene (Pyr) in a 30-cm peat profile from the Altay Mountain, northwestern China. Our results revealed concentrations of BC from 11.71 to 67.5 mg·g −1 , and PAHs from 168.09 to 263.53 ng·g −1 . The δ 13 C BC value ranged from − 31.37 to − 26.27‰, with an average of − 29.54‰, indicating that the BC mainly comes from biomass combustion. The ratios of BaA/(BaA + Chr), Flt/(Flt + Pyr), and Ant/(Ant + Phe) exceeded 0.35, 0.5, and 0.1, respectively, revealing that the PAHs pollutants mainly originated from the combustion of biomass and fossil fuel burning. Furthermore, based on these findings and our knowledge of social development in Altay, industrial transport and tourism have influenced the emission, transport, and deposition of BC and PAH in peatlands in the Altay mountains since the 1980s. After 1980, pollutant concentrations decreased with the implementation of environmental policies. The results not only reveal the influence of anthropogenic activities on the sedimentary characteristics of peatlands in the Altay Mountains, but also provide an important theoretical basis for the conservation of fragile mountain peatlands.

Effect of sludge redistribution strategy on stability of partial nitrification-anammox process: Further exploration of the potential value of sludge - Peng Wang; Rui Ou; Jun Tan; Ning Li; Min Zheng; Qinghai Jin; Jin Yu; Di He (Chemosphere, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Enhancing the effluent prediction accuracy with insufficient data based on transfer learning and LSTM algorithm in WWTPs - Yadan Yu; Yangwu Chen; Shunbo Huang; Rui Wang; Yadong Wu; Houzhen Zhou; Xin Li; Zhouliang Tan (Journal of Water Process Engineering, 2024)

Comparative toxicology of algal cell extracts and pure cyanotoxins: insights into toxic effects and mechanisms of harmful cyanobacteria Raphidiopsis raciborskii - Zhongshi He; Youxin Chen; Jin Gao; Yewei Xu; Xinya Zhou; Rui Yang; Ruozhen Geng; Renhui Li; Gongliang Yu (Harmful Algae, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

A functional Pickering emulsion coating based on octadecenylsuccinic anhydride modified γ-cyclodextrin metal-organic frameworks for food preservation - Yannan Zhang; Dehai Yu; Rui Zhao; Zhuo Li; Baoting Dong; Feihong Hu; Shan Li; Fengshan Zhang; Huili Wang (Food Hydrocolloids, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

The carbon dots with near-infrared electrochemiluminescence emission and low excitation potential for ultrasensitive analysis of microRNA-222 - Yu-Zhuo Guo; Rui Liu; Ying Zeng; Ye-Yu Liao; Jia-Li Liu; Ya-Qin Chai; Ruo Yuan (Chemical Engineering Journal, 2024)

Revealing the electrochemical-mechanical correspondence between electrode films and 20 Ah prismatic Li-ion batteries via optical fiber monitoring - Xiaoyu Ge; Yi Zhang; Rui Du; Nian Chen; Yifei Yu; Zhen Li; Yunhui Huang (Chemical Engineering Journal, 2024)

Carboxymethyl chitosan-based hydrogel-Janus nanofiber scaffolds with unidirectional storage-drainage of biofluid for accelerating full-thickness wound healing - Xinhao Chen; Hui Huang; Xinru Song; Ting Dong; Jiafei Yu; Jieyan Xu; Rui Cheng; Tingting Cui; Jun Li (Carbohydrate Polymers, 2024)

Refining granite generation by interrogation of zircon and monazite U-Th-Pb and Hf/Nd-O isotopes - Xing Zhang; Yuanbao Wu; Bin Fu; Wenxiang Zhang; Long Li; Guangyan Zhou; Rui Li; Zhaochu Hu; Yu He; Zhengwei Qin (Chemical Geology, 2024)

Morusin inhibits breast cancer-induced osteolysis by decreasing phosphatidylinositol 3-kinase (PI3K)-mTOR signalling - Long Zhang; Weibin Li; Xiaohui Chen; Dongmin Cao; Siyuan You; Fan Shi; Zhengqiong Luo; Hongyu Li; Xiangchen Zeng; Yabin Song; Na Li; Yoshie Akimoto; et al. (Chemico-Biological Interactions, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Integration of the Metabolome and Transcriptome Reveals Diurnal Variability in the Effects of Melatonin on Salt Tolerance in Maize Seedlings - Jiajie Wang; Di Yan; Zhenzong Lu; Rui Liu; Yue Hong; Ye Wang; Zhen Peng; Chunxin Yu; Yuerong Gao; Ziyan Liu; Liusheng Duan; Runzhi Li (Journal of Plant Growth Regulation, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Taxonomic status of hares ( Lepus spp.) in Xinjiang, China (Lagomorpha: Leporidae): An integrative approach - Wen‐Juan Shan; Zu‐Rui Li; Hui‐Ying Dai; Peng‐Cheng Dong; Yu‐Cong Zhang (Zoologica Scripta, 2024)
The taxonomic status and interspecies relationships of hares (genus Lepus ) in Xinjiang, China, remain ambiguous owing to extremely similar external morphologies, introgressive hybridization between species and a lack of molecular genetic records. In this study, a total of 154 hare specimens were used to clarify their taxonomic status. Based on multiple lines of evidence, including observations and comparisons of external morphological characteristics, skull morphometrics and genome‐wide single nucleotide polymorphism (SNP) datasets, four hare species were recognised. Lepus yarkandensis and Lepus timidus , which have obvious morphological characteristics, were identified as two distinct species, as previously reported. Combining the integrated morphological and molecular datasets with the relevant literature, we proposed suggestions on the classification of the more controversial hares. Due to molecular and morphological similarities, hares in northern and central Xinjiang were divided into two subspecies of Lepus tolai , namely, Lepus tolai lehmanni and Lepus tolai centrasiaticus . Despite similar external morphological characters, hares in the southwest Pamir Plateau and its surroundings can be distinguished from L. tolai by differences in skull morphology and genetic divergence and were, therefore, considered a subspecies of Lepus tibetanus , Lepus tibetanus pamirensis . Furthermore, we found that hybridization and introgression occurred between sympatric or parapatric hares, especially between L. yarkandensis and L. tibetanus pamirensis , L. yarkandensis and L. tolai centrasiaticus , and L. tolai lehmanni and L. timidus .

Brain-Derived Exosomal CircRNAs in Plasma Serve as Diagnostic Biomarkers for Acute Ischemic Stroke - Xinli Jiang; Rui Zhang; Geng Lu; Yu Zhou; Jianfeng Li; Xinrui Jiang; Shuangshuang Gu; Hongwei Liang; Jun Wang (Journal of Neuroimmune Pharmacology, 2024)

Integrated rice-yellow catfish farming resulting in variations in the agricultural environment, rice growth performance, and soil bacterial communities - Yiran Hou; Zhaoxiong Yu; Rui Jia; Bing Li; Jian Zhu (Environmental Science and Pollution Research, 2024)

A quantitative digital twin maturity model for underground infrastructure based on D-ANP - Tao Li; Yi Rui; Sicheng Zhao; Yu Zhang; Hehua Zhu; Xiaojun li (Tunnelling and Underground Space Technology, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Association between ambient PM1 and the prevalence of chronic kidney disease in China: A nationwide study - Rui Chen; Chao Yang; Yuming Guo; Gongbo Chen; Shanshan Li; Pengfei Li; Jinwei Wang; Ruogu Meng; Huai-yu Wang; Suyuan Peng; Xiaoyu Sun; Fulin Wang; et al. (Journal of Hazardous Materials, 2024)

Enhancing methanol tolerance of Thermomyces lanuginosus lipase by rational design and biodiesel production through one-step feeding of methanol - Pingping Qu; Raudah Lazim; Dongdong Li; Rui Xu; Fei Wang; Xun Li; Yu Zhang (Journal of Cleaner Production, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

A polypyrrole-dopamine/poly(vinyl alcohol) anisotropic hydrogel for strain sensor and bioelectrodes - Shuang Chen; Bingyan Guo; Jiajun Yu; Zhuojun Yan; Rui Liu; Chaojie Yu; Zhongming Zhao; Hong Zhang; Fanglian Yao; Junjie Li (Chemical Engineering Journal, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Hollow AMn2O4-δ (A = Co, Zn, Ni) nanotube for direct photo-oxidation of methane to C1 and C2 alcohols at atmospheric pressure and room temperature - Jun Duan; Shiying Fan; Xinyong Li; Jing Wang; Chunpeng Bai; Shixuan Yu; Weitong Ling; Rui Tian; Dongke Zhang (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Intercropping efficiently utilizes phosphorus resource in soil via different strategies mediated by crop traits and species combination - Ran An; Rui-Peng Yu; Yi Xing; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Plant and Soil, 2024)

Study on physiological and biochemical characteristics during in vitro flowering of Rosa ‘Yametsu-Hime’ - Meijing Yuan; Shengdie Weng; Yu Ma; Rui Wu; Xiaoling Kang; Li Du (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Holocene overflow events of the lower Yellow River recorded in Huangdun ancient lake, northern Jiangsu Plain, China - Rui Zhang; Li Xing; Shi‐Yong Yu; Junsheng Nie; Jinjia Wu; Zhao Wang; Shiyue Chen; Zhanfang Hou; Guodong Zhang; Denghui Zhang (Journal of Quaternary Science, 2024)
Overflow events are important embodiments of the evolutionary characteristics of the lower Yellow River. Lakes in the lower reaches of the Yellow River have the capacity to record these events. Due to the complex provenance and transport pathways of sediments in local lakes, it is difficult to extract reliable information on sediments delivered by the Yellow River based on conventional methods and proxies. Here, we show results from a genetically meaningful end‐member (EM) decomposition of sediment grain‐size data from Huangdun ancient lake. The grain‐size of the sediments can be decomposed into three end‐members. Comprehensive analysis combining environmental magnetism and geochemical indicators clarifies the significance of each end‐member. EM1 represents mixed signals of various proximal fluvial sediments and the Yellow River materials. EM2 is similar to terrestrial fine‐grained debris in conjunction with local pedogenic materials, aeolian inputs and some Yi River materials. EM3 represents a component that is mainly derived from long‐distance transport by the lower Yellow River. End‐member analysis successfully identified overflow events of the lower Yellow River on a southward‐flowing path during the Holocene. This study provides a meaningful attempt to reconstruct the evolutionary history of the lower Yellow River from sedimentary records.

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Transcriptomic analysis of hydrogen peroxide-induced liver dysfunction in Cyprinus carpio: Insights into protein synthesis and metabolism - Wenrong Feng; Yuanfeng Xu; Shengyan Su; Fan Yu; Jianlin Li; Rui Jia; Changyou Song; Hongxia Li; Pao Xu; Yongkai Tang (Science of The Total Environment, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Towards energy conservation and carbon reduction for wastewater treatment processes: A review of carbon-neutral anaerobic biotechnologies - Xinzheng Zhang; Tianwei Hao; Tao Zhang; Yong Hu; Rui Lu; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Journal of Water Process Engineering, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Factors affecting chemical and textural properties of dried tuber, fruit and vegetable - Yue Li; Han Zhao; Kexin Xiang; Dajing Li; Chunju Liu; Haiou Wang; Wenqian Pang; Liying Niu; Rui Yu; Xiyun Sun (Journal of Food Engineering, 2024)

Tracing spatial patterns of lacustrine groundwater discharge in a closed inland lake using stable isotopes - Xiaohui Ren; Ruihong Yu; Rui Wang; Jianfang Kang; Xiangwei Li; Pengxuan Zhang; Tingxi Liu (Journal of Environmental Management, 2024)

Regulatory effect of trehalose metabolism on chitin synthesis in Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) as determined using RNAi - Yan-qi Yang; Yu-jian Liang; Jun-rui Zhi; Ding-yin Li; Cao Li (Journal of Asia-Pacific Entomology, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Decoding the interaction mechanism between bis(2-methyl-3-furyl) disulfide and oral mucin - Yu Xi; Meihong Yu; Rui Cao; Xuejie Li; Xiangquan Zeng; Jian Li (Food Chemistry, 2024)

Oxidative stress-activated Nrf2 remitted polystyrene nanoplastic-induced mitochondrial damage and inflammatory response in HepG2 cells - Menghao Guo; Yunjing Li; Shuyan Niu; Rui Zhang; Xin Shen; Yu Ma; Liqing Wu; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Environmental Toxicology and Pharmacology, 2024)

Effective value-added strategy of furan compounds with short straight-chain monohydric alcohols based on acid site regulation of zirconium based mesoporous carbon - Jian Xiong; Liying Li; Xuebin Lu; Lei Ye; Zhihao Yu; Wei Li; Ming Zhang; Yiming Li; Jiao Tao; Rui Zhang; Yina Qiao (Biomass and Bioenergy, 2024)

Aerosol effects on the three-dimensional structure of organized precipitation systems over Beijing-Tianjin-Hebei region in summer - Jing Xi; Rui Li; Xiaoye Fan; Yu Wang (Atmospheric Research, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Towards carbon-neutral biotechnologies for rural wastewater: A review of current treatment processes and future perspectives - Xinzheng Zhang; Guangyi Ma; Tao Chen; Churen Yan; Yiheng Chen; Qinye Wang; Xinyu Peng; Wenjie Xu; Tianwei Hao; Tao Zhang; Rui Lu; Dapeng Li; et al. (Journal of Water Process Engineering, 2024)

Screening the phytotoxicity of micro/nanoplastics through non-targeted metallomics with synchrotron radiation X-ray fluorescence and deep learning: Taking micro/nano polyethylene terephthalate as an example - Hongxin Xie; Chaojie Wei; Wei Wang; Rui Chen; Liwei Cui; Liming Wang; Dongliang Chen; Yong-Liang Yu; Bai Li; Yu-Feng Li (Journal of Hazardous Materials, 2024)

Preparation of conjugated linoleic acid-rich oleogel emulsions by dynamic high-pressure microfluidization technology - Dianyu Yu; Na Li; Rui Wang; Wenlin Xue; Donghua Wang; Walid Elfalleh; Lanxia Qin; Fengying Xie (Journal of Food Engineering, 2024)

Experimental study on the mass burning rate and flame tilt angle of annular pool fires under cross air flow - Ping Huang; Rui Zhang; Chunxiang Liu; Xinyue Wu; Shanshan Chen; Jinhao Li; Man Li; Longxing Yu (Fuel, 2024)

GC-IMS determination of volatile organic compounds as potential indicators of wheat germination rate - Yu Liu; Shuwei Ren; Qianqian Sun; Boli Guo; Yingquan Zhang; Ming Li; Rui Zhang (Food Bioscience, 2024)

Characteristics, sources, and health risk assessment of atmospheric particulate mercury in Guanzhong Basin - Xiaofei Li; Rui Zhang; Lekhendra Tripathee; Feng Yu; Jingning Guo; Wen Yang; Junming Guo; Shichang Kang; Junji Cao (Environmental Pollution, 2024)

Grazing reduced greenhouse gas fluxes in Inner Mongolia grasslands: A meta-analysis - Peidong Yu; Hasbagan Ganjurjav; Guozheng Hu; Mingjie Li; Zhiqiang Wan; Guoxu Ji; Rui Gu; Qingzhu Gao (Ecological Engineering, 2024)

HNF4A as a potential target of PFOA and PFOS leading to hepatic steatosis: Integrated molecular docking, molecular dynamic and transcriptomic analyses - Rui Li; Zijing Zhang; Yuxin Xuan; Yulu Wang; Yuyan Zhong; Lingyin Zhang; Jinrui Zhang; Qian Chen; Shuling Yu; Jintao Yuan (Chemico-Biological Interactions, 2024)

Improving bioelectrochemical performance by sulfur-doped titanium dioxide cooperated with Zirconium based metal–organic framework (S-TiO2@MOF-808) as cathode in microbial fuel cells - Qin Qi; Guofu Huang; Rui Li; Jiale Yu; Xiaomin Chen; Zhen Liu; Yanyan Liu; Renjun Wang; Yuewei Yang; Junfeng Chen (Bioresource Technology, 2024)

Investigating the Immunogenic Cell Death-Dependent Subtypes and Prognostic Signature of Triple-Negative Breast Cancer - Youyang Shi; Yuanyuan Wu; Feifei Li; Kexin Jiang; Xiaofang Fang; Yu Wang; Xiaoyun Song; Rui Wang; Lixin Chen; Jinzhou Zheng; Chunyu Wu; Yuenong Qin; et al. (Phenomics, 2024)

Molecular characterization of a novel mycovirus from binucleate Rhizoctonia AG-A strain A46 - Rui Shi; Xiaohan Mo; Zebin Chen; Wurong Chen; Shuhui Yu; He Liu; Yuchuan Li; Lili Dai; Yanqiong Li (Archives of Virology, 2024)

Diversified cropping systems with complementary root growth strategies improve crop adaptation to and remediation of hostile soils - Wei-Ping Zhang; Surigaoge Surigaoge; Hao Yang; Rui-Peng Yu; Jin-Pu Wu; Yi Xing; Yinglong Chen; Long Li (Plant and Soil, 2024)

Influences of hydrodynamics on microbial community assembly and organic carbon composition of resuspended sediments in shallow marginal seas - Yangli Che; Chaoran Lin; Shen Li; Jiao Liu; Longhai Zhu; Shilei Yu; Nan Wang; Haoshuai Li; Mutai Bao; Yang Zhou; Tonghao Si; Rui Bao (Water Research, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Pathways for regions to achieve carbon emission peak: New insights from the four economic growth poles in China - Yu-Jie Hu; Fali Duan; Honglei Wang; Chengjiang Li; Rui Zhang; Bao-Jun Tang (Science of The Total Environment, 2024)

Soil phosphorus availability mediates the effects of nitrogen addition on community- and species-level phosphorus-acquisition strategies in alpine grasslands - Zhen-Huan Guan; Zuonan Cao; Xiao Gang Li; Thomas Scholten; Peter Kühn; Lin Wang; Rui-Peng Yu; Jin-Sheng He (Science of The Total Environment, 2024)

RETRACTED: Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2024)

Fungus reduces tetracycline-resistant genes in manure treatment by predation of bacteria - Lei Liu; Qianxi Yin; Yu Hou; Rui Ma; Yi Li; Zhenyu Wang; Ganggang Yang; Yu Liu; Hailei Wang (Science of The Total Environment, 2024)

Polysulfide regulation by defect-modulated Ta3N5− electrocatalyst toward superior room-temperature sodium-sulfur batteries - Zhen Zhang; Dan Luo; Jun Chen; Chuyin Ma; Matthew Li; Haoze Zhang; Renfei Feng; Rui Gao; Haozhen Dou; Aiping Yu; Xin Wang; Zhongwei Chen (Science Bulletin, 2024)

Nano-selenium repaired the damage caused by fungicides on strawberry flavor quality and antioxidant capacity by regulating ABA biosynthesis and ripening-related transcription factors - Yuping Liu; Rui Liu; Feifei Li; Simin Yu; Yufan Nie; Jia-Qi Li; Canping Pan; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Pesticide Biochemistry and Physiology, 2024)

Meteoric diagenesis influenced by East Asian Summer Monsoon: A case study from the Pleistocene carbonate succession, Xisha Islands, South China Sea - Lü Wu; Rui Wang; Kefu Yu; Min Ren; Simone Booker; Ruoxia Shen; Wei Jiang; Shendong Xu; Tianlai Fan; Songye Wu; Qiushuang Qin; Xingchi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Revealing the membrane fouling behavior and interfacial interaction mechanism in a combined visible light photocatalysis-ultrafiltration system for advanced purification of NOM - Rui Yu; Yanling Yang; Liping Tian; Xing Li; Chunjiao Liu; Tianjie Sun; Haiqing Chang; Zhiwei Zhou (Journal of Water Process Engineering, 2024)

Synergizing policies for carbon reduction, energy transition and pollution control: Evidence from Chinese power generation industry - Yu-Jie Hu; Rui Zhang; Honglei Wang; Chengjiang Li; Bao-Jun Tang (Journal of Cleaner Production, 2024)

Revisiting the porter hypothesis within the economy-environment-health framework: Empirical analysis from a multidimensional perspective - Xialing Sun; Rui Zhang; Zhaofeng Yu; Shichao Zhu; Xiaotong Qie; Jiaxi Wu; Pengpeng Li (Journal of Environmental Management, 2024)

Study on barrier mechanism and application of silico-alkaline sol-modified bentonite cutoff wall materials to lead pollution in lead-zinc tailings pond - Rui Zhu; Changwen Ye; Bo Yu; Weiming Tao; Zhidong Zhou; Jie Li (Journal of Contaminant Hydrology, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Enhanced selective production of aldehydes and ketones by catalytic upgrading of pyrolysis vapor from holocellulose over red mud-based composite catalysts - Shanshan Shao; Yu Cao; Zian Ye; Xiaohua Li; Huiyan Zhang; Rui Xiao (Fuel, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Membrane fouling mitigation and EPS reduction by CNTs-TiO2-PEDOT modified anode-membrane in Membrane Electro-Bioreactor (MEBR) treating mariculture wastewater - Jing Song; Yihan Li; Shihan Wang; Rui Han; Yu Ba; Ying Liu; Shengqiang Fan (Desalination, 2024)

Exosome as non-invasive prognostic and diagnostic biomarker and nanovesicle for targeted therapy of non-small cell lung carcinoma - Zhao Yang; Shi Fu; Yongchao Li; Youfeng Liang; Mingxuan Hao; Rui Guo; Changyuan Yu; Zahid Hussain; Jinku Zhang; Haifeng Wang (Chemical Engineering Journal, 2024)

Sulfite activation of Fe-Mn bimetallic oxides for rapid oxidative removal of As(III) in water: Involvement of active Mn(III) - Guiyuan Cai; Yu Tian; Lipin Li; Wenxuan Zhang; Rui Huang; Jun Zhang; Qinyu Wang; Hua Xu; Yifeng Zhang (Chemical Engineering Journal, 2024)

Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2024)

RLP system: A single-tube two-step approach with dual amplification cascades for rapid identification of EGFR T790M - Tao Huang; Yanxi Han; Yuqing Chen; Zhenli Diao; Yu Ma; Lei Feng; Duo Wang; Rui Zhang; Jinming Li (Analytica Chimica Acta, 2024)

Imperfect but effective crypsis and flower-visiting strategy in a crab spider - Zichang Li; Long Yu; Guocheng Yu; Rui Zhong; Yao Zhao; Jie Liu; Yu Peng (Behavioral Ecology and Sociobiology, 2024)